Infrared temperature measurements on high pressure turbine blades in the Oxford Turbine Research Facility: calibration and image processing techniques - Sisti, M; Falsetti, C; Beard, P; Chana, K (European Turbomachinery Society, 2021)
This paper presents the calibration method and error evaluation for an infrared (IR) measurement system implemented on the upgraded Oxford Turbine Research Facility (OTRF). The OTRF is a world leading turbine test facility capable of matching engine representative conditions of Reynolds and Mach numbers, non-dimensional speed and gas-to-wall temperature ratio. Infrared measurements will provide temperature maps on high-pressure (HP) turbine blades permitting full surface evaluation of metal effectiveness at engine representative conditions for the first time. The test environment presents significant challenges for accurate IR thermography measurements. High temperature of neighboring components causes high reflected radiation to reach the IR detector offsetting the measurement, whilst high blade velocity (~200 ms‑1) challenges clear image acquisition. Using a bespoke calibration facility, an IR thermography calibration procedure was assessed to evaluate the surface emissivity of the target, the transmissivity of the optical path, and the erroneous reflected radiation. A MATLAB code was developed to address the blurring problem caused by the target high speed. The results of this study will allow an advanced and highly accurate IR measurement system to be implemented in the upgraded OTRF.